Corporate Governance and Its Relationship with Financial Performance in Iraq - Ahmed, Amanj Mohamed; Hágen, István (Acta Carolus Robertus, 2023)
It is expected that banks should operate with a recognized standard of corporate governance. The importance of excellent governance processes in banks cannot be overstated because they are essential to gain and maintain the confidence and the customers satisfaction. This paper aims to explore the relationship between corporate governance (CG) and financial performance (FP) of Iraqi listed banks. To obtain this goal, two econometric models were enhanced to measure the association between the variables by applying multiple linear regression. The secondary data was obtained from the audited annual financial statement of ten listed banks in the Iraqi stock exchange in the period 2017-2021. Four corporate governance proxies, such as (CEO Duality, board size, audit committee meetings and independent board) are tested on two indicators of financial performance (return on assets and return on equity). The finding illustrated that CEO Duality, board size, and audit committee meetings have a positive and significant influence on the financial performance of banks. On the other hand, a negative and significant association can be observed between the independent boards and banks’ financial performance. Hence, the study pointed out that the financial performance of banking industry has been impacted by all of the components of corporate governance selected in this research.
Keywords: corporate governance; financial performance; Iraqi listed banks